2016
DOI: 10.3389/fpls.2016.00230
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide Signaling in Plant Development and Abiotic Responses: Crosstalk with Nitric Oxide and Calcium

Abstract: Hydrogen peroxide (H2O2), as a reactive oxygen species, is widely generated in many biological systems. It has been considered as an important signaling molecule that mediates various physiological and biochemical processes in plants. Normal metabolism in plant cells results in H2O2 generation, from a variety of sources. Also, it is now clear that nitric oxide (NO) and calcium (Ca2+) function as signaling molecules in plants. Both H2O2 and NO are involved in plant development and abiotic responses. A wide rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
184
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(188 citation statements)
references
References 129 publications
3
184
1
Order By: Relevance
“…Intracellular Ca 2+ increases were reported to be a consequence of an uptake from the extracellular space or due to Ca 2+ liberation from intracellular stores. Therefore, NO Results of the present study show that NO and H 2 O 2 mediate SO 2 toxicity via Ca 2+ -dependent pathway, which is consistent with previous reports showing that NO and H 2 O 2 act via Ca 2+ signaling pathways in plants responding to abiotic stress (Pei et al 2000;Qiao and Fan 2014;Niu and Liao 2016). These results will broaden our understanding on how plants respond to environmental stress.…”
Section: Discussionsupporting
confidence: 92%
“…Intracellular Ca 2+ increases were reported to be a consequence of an uptake from the extracellular space or due to Ca 2+ liberation from intracellular stores. Therefore, NO Results of the present study show that NO and H 2 O 2 mediate SO 2 toxicity via Ca 2+ -dependent pathway, which is consistent with previous reports showing that NO and H 2 O 2 act via Ca 2+ signaling pathways in plants responding to abiotic stress (Pei et al 2000;Qiao and Fan 2014;Niu and Liao 2016). These results will broaden our understanding on how plants respond to environmental stress.…”
Section: Discussionsupporting
confidence: 92%
“…Polyamine oxidase catalyses Spd or Spm oxidation for production of H 2 O 2 . H 2 O 2 is signalling to regulate expression of numerous genes relative to stress responses (Niu & Liao, ). H 2 O 2 is accumulated as a result of induced PAO activity that leads to Spd and Spm oxidation in MfSAMS1 transgenic tobacco plants and induces gene expression with enhanced activities of antioxidant enzymes (Guo et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work also showed that heat shock could improve the resistance of maize seedlings to heat, chilling, salt, and drought stress (Gong et al, 2001). Numerous studies found that the acquisition of stress tolerance including cross-adaptation was involved in a complex signal network consisting of many second messengers such as Ca 2+ , abscisic acid (ABA), hydrogen peroxide (H 2 O 2 ) and nitric oxide (NO), as well as their crosstalk (Knight, 2000; Pandey, 2015; Li and Gu, 2016; Li and Jin, 2016; Niu and Liao, 2016; Wang et al, 2016). In tobacco, mechanical stimulation can successively trigger H 2 O 2 and NO signaling (Li and Gong, 2011, 2013), heat shock can induce Ca 2+ and ABA signaling one after the other (Gong et al, 1998a,b), which in turn induce cross-adaptation to heat and chilling stress, similar results were reported by Gong et al (2001) in maize seedlings.…”
Section: Introductionmentioning
confidence: 99%